160. Kilovoltage rotational radiotherapy of breast cancer with synchrotron radiation: A phantom study with 100 keV and 6 MV VMAT dose delivery. (December 2018) - Masi, M.; Castriconi, R.; Di Lillo, F.; Sarno, A.; Mettivier, G.; Perna, L.; Cattaneo, M.; Fiorino, C.; Calandrino, R.; Russo, P.
Abstract : Purpose: We proposed a new technique for breast cancer rotational radiotherapy using kilovoltage synchrotron radiation (SR)[1] . Here, we compared 2D dose distributions in a breast phantom at 6 MV in circular orbit Volumetric Arc Therapy (VMAT) with respect to 100 keV irradiation in rotational radiotherapy with SR. Methods: The dose distribution was evaluated with calibrated EBT3 radiochromic films inserted at midplane in a 14-cm diameter PMMA cylindrical phantom, simulating the pendant breast. We irradiated a cylindrical target (15 × 20 mm 2 (W × H)) at the centre of phantom. Measurements were performed at the Imaging and Medical Beamline (Australian Synchrotron, Clayton, Australia) at 100 keV, with a SR beam of size 15  ×  20 mm 2 (W  ×  H) continuously irradiating the phantom during a 360 deg rotation around the cylinder axis with a central dose to the target of 7 Gy. Megavoltage measurements were performed at 6 MV using a Varian Clinac iX System Linac, with a target dose of 6 Gy. Results: The principle of dose summation along the axis of rotation produced a dose distribution peaked at the centre of rotation for small fields. The target-to-surface dose ratio was 20:1 at 6 MV and 9:1 at 100 keV, for a target at the center of the phantom. Conclusions: We performed a feasibility test of kilovoltage rotational radiotherapy dedicated to the breast showing a target-to-surface dose ratio higher than with MV radiotherapy but still acceptable for skin tissue sparing.